Peripheral odontogenic fibroma an uncommonly overviewed benign neoplasm: A case report and review of literature - Pasalkar, Lavanya; Bhujbal, Prathmesh; Sonawane, Shrutika; Khare, Vikram (Indian Journal of Case Reports, 2022)
Peripheral odontogenic tumors (POTs) are one of the rare neoplasms to occur on the gingiva. Peripheral odontogenic fibroma (POdF) is the most common POT constituting a prevalence of 1.2%. A plethora of lesions sharing similar clinical features makes the diagnosis difficult. Histopathological examination plays a key role in these types of cases. Here, we present a rare case of POdF in a 36-year-old female patient with a lobulated pebbled-like exophytic growth on the right gingiva. Histopathological investigation showed the presence of odontogenic epithelium and dystrophic calcification which are the pathognomonic features of POdF. After surgical removal, POdF is seen to recur, but the exact recurrence rate cannot be estimated due to the scarcity of reported cases. In this case, follow-up of the patient showed no recurrence at 6, 12, and 18 months post-surgery.